The effects of distance learning on adolescents' relationships and emotional well-being - Marco D'Agostini; Damiano Cantone; Stefania Pascut; Andrea Paschetto; Susanna Feruglio (Firenze University Press, 2022)
In this study, conducted on over 1300 students from second level secondary schools in the province of Udine, investigate the impact of distance learning (DAD) on relationships and emotional well-being. The analysis of two questionnaires filled out anonymously by students, highlighted a significant experience of suffering that opens up a critical reflection on the challenges that the school system is called to face since the end of the pandemic.   Le ricadute della Didattica a Distanza sulle relazioni e sul benessere emotivo degli adolescenti. In questo studio, condotto su oltre 1300 studenti/esse delle scuole secondarie di secondo grado della provincia di Udine, è stato indagato l'impatto della didattica a distanza (DAD) sulle relazioni e sul benessere emotivo. L'analisi di due questionari compilati anonimamente da studentesse e studenti ha messo in luce un rilevante vissuto di sofferenza che apre una riflessione critica sulle sfide che il sistema scolastico è chiamato ad affrontare dalla fine della pandemia.